2017
DOI: 10.1177/0961203317726378
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the changes of ovarian reserve, menstruation, and lymphocyte subpopulation in systemic lupus erythematosus (SLE) patients of childbearing age

Abstract: Objective The main aim of this study was to investigate the ovarian reserve, menstruation, and lymphocyte subpopulation in systemic lupus erythematosus (SLE) patients of childbearing age. Methods We enrolled 40 SLE patients of childbearing age and 40 age-matched healthy controls. Anti-Müllerian hormone (AMH) was tested by electrochemiluminescence, and lymphocyte subsets were tested by flow cytometry. Menstruation situation was obtained by interview. Results The AMH level of the SLE group was significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Previous reports showed that serum AMH levels were lower in SLE patients ( 33 , 35 , 37 ). However, other studies reported that patients with SLE do not display significant alterations in the OR ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous reports showed that serum AMH levels were lower in SLE patients ( 33 , 35 , 37 ). However, other studies reported that patients with SLE do not display significant alterations in the OR ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 84%
“…Usually, the low AMH levels in SLE patients have been dichotomized for the presence of menstrual alterations, finding that the patients with abnormal menstruation had lower AMH levels than those of SLE patients without menstrual alterations ( 35 ). However, this has not been observed consistently ( 37 , 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AMH has been considered as a reliable biomarker of ovarian function. According to our previous study and other studies, AMH was significantly decreased in SLE patients 14,15 …”
Section: Introductionmentioning
confidence: 55%
“…Decrease in the ovarian reserves is independently associated with presence of autoimmune disease, with low Anti-Mullerian hormone levels noted especially in SLE 3,[19][20][21] however; the impact on fertility may be compounded with use of alkylating agents, especially cyclophosphamide. The effect of cyclophosphamide on fertility is impacted by the age of patient at the time of exposure to the medication and dose of cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%